2022
DOI: 10.1038/s41419-022-04901-x
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A promotes the metastasis of esophageal squamous cell carcinoma by activating the HDAC7/SNAIL signaling pathway

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common cancers worldwide, with high incidence and mortality rates and low survival rates. However, the detailed molecular mechanism of ESCC progression remains unclear. Here, we first showed significantly higher WNT5A and SNAIL expression in ESCC samples than in corresponding paracancerous samples. High WNT5A and SNAIL expression levels correlated positively with lymphatic metastasis and poor prognosis for patients with ESCC based on immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Studies have also reported that HDAC7 is crucial in cancer metastasis, for instance, in breast cancer, nasopharyngeal cancer, and ovarian cancer [17,22]. A previous study verified that HDAC7 dramatically increases Snail levels and decreases E-cadherin levels, further promoting the migration and invasion of ESCC [19]. Our current study revealed that HDAC7 overexpression promotes the metastasis of CM cells, which was validated by wound healing and transwell assays.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Studies have also reported that HDAC7 is crucial in cancer metastasis, for instance, in breast cancer, nasopharyngeal cancer, and ovarian cancer [17,22]. A previous study verified that HDAC7 dramatically increases Snail levels and decreases E-cadherin levels, further promoting the migration and invasion of ESCC [19]. Our current study revealed that HDAC7 overexpression promotes the metastasis of CM cells, which was validated by wound healing and transwell assays.…”
Section: Discussionsupporting
confidence: 81%
“…Dysregulated HDAC7 expression has been validated in various cancers, such as ovarian cancer, and glioma. HDAC7 overexpression contributes to migration and is linked with a poor prognosis in lung cancer, nasopharyngeal carcinoma, and esophageal squamous cell carcinoma (ESCC) [ 17 19 ]. In the present study, the IHC analysis results based on 16 paired CM tumors and normal samples showed that the HDAC7 level was significantly higher in CM tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mechanisms through which EMT is induced by HDAC7 or TTYH3, further investigations have yet been conducted by us. However, Feng et al 34 demonstrated the impact of HDAC7 on EMT by upregulating Snail. Specially, Wang et al 14 have reported that TTYH3 can impact EMT through GSK3-β/β-catenin pathway in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that melatonin, a hormone produced by the pineal gland, could hinder the growth of ESCC tumor by reducing the activity of the HDAC7/β-catenin/c-myc positive feedback loop and suppressing the function of USP10 that is responsible for maintaining the stability of HDAC7 protein ( 35 ). An additional mechanism of ESCC has been elucidated, indicating the involvement of HDAC7 in the metastasis of tumor cells mediated by WNT5A ( 49 ). These studies reveal tumorigenesis originates from the loss of the body’s constraints on oncogenic factors.…”
Section: The Involvement Of Hdac7 In Cancermentioning
confidence: 99%